2018
DOI: 10.1021/acs.inorgchem.8b01489
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on Reactions of Group 13 Diyls with Tetraorganodipentelanes

Abstract: LGa {L = HC[C(Me)N(2,6- iPrCH)]} reversibly reacts with EPh (E = Sb, Bi) in a temperature-dependent equilibrium reaction with insertion into the E-E bond and formation of LGa(EPh) (E = Sb 1, Bi 2). Analogous findings were observed in the reactions of LGa {L = (CH)NC[N(2,6- iPrCH)]} with ER (R = Ph, Et), yielding LGa(EPh) (E = Sb 3, Bi 4) and LGa(EEt) (E = Sb 5, Bi 6). 1-3 and 5 were isolated by fractional crystallization at low temperature, whereas 4 and 6 could not be isolated in their pure form even at low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…The M–E bond lengths successively increase in the order of Ga–As < Al–As < In–As < Ga–Sb < Al–Sb < In–Sb, in good agreement with the sum of the calculated covalent radii (Σ r cov (Ga–As) = 2.45 Å, Σ r cov (Al–As) = 2.47 Å, Σ r cov (In–As) = 2.63 Å, Σ r cov (Ga–Sb) = 2.64 Å, Σ r cov (Al–Sb) = 2.66 Å, Σ r cov (In–Sb) = 2.82 Å). [ 12 ] Moreover, the M–E bond lengths are in accordance with previously reported bond lengths in [L(X)M]‐substituted pnictanes, dipnictenes and pnictanyl radicals (Al–As 2.4501(7) Å, 2.4554(7) Å; [ 16a ] Ga–As 2.3957(5)‐2.5197(3) Å; [ 16a,18c ] Al–Sb 2.6586(7) Å, 2.7169(7) Å; [ 24 ] Ga–Sb 2.5478(6)–2.8458(13) Å; [ 19,25 ] In–Sb 2.7250(4)‐2.8340(2) Å [ 9c ] ). The As1–C40(Ph) bond lengths in 3 – 5 are comparable to those of Al and Ga‐substituted arsanes Tmp 2 AlAsPh 2 (1.953 Å, 1.966 Å; Tmp = N[C(Me) 2 CH 2 ]CH 2 ), [ 26 ] (Mes*AlAsPh) 3 (1.957(8) Å, 1.971(7) Å, 1.959(7) Å, Mes* = 2,4,6‐ t Bu 3 C 6 H 2 ), [ 27 ] and (Tip 2 Ga) 2 AsPh (1.950(7) Å, Tip = 2,4,6‐ i Pr 2 C 6 H 2 ), [ 28 ] while the Sb1–C40(Ph) bond lengths in 6 – 8 compare well to those of I (2.1716(16) Å), [ 19 ] II (2.1804(18) Å, 2.1748(18) Å), [ 20 ] and [L(Cl)Ga]Sb(Cl)Dip (2.1891(11) Å, 2.1725(13) Å).…”
Section: Resultssupporting
confidence: 89%
“…The M–E bond lengths successively increase in the order of Ga–As < Al–As < In–As < Ga–Sb < Al–Sb < In–Sb, in good agreement with the sum of the calculated covalent radii (Σ r cov (Ga–As) = 2.45 Å, Σ r cov (Al–As) = 2.47 Å, Σ r cov (In–As) = 2.63 Å, Σ r cov (Ga–Sb) = 2.64 Å, Σ r cov (Al–Sb) = 2.66 Å, Σ r cov (In–Sb) = 2.82 Å). [ 12 ] Moreover, the M–E bond lengths are in accordance with previously reported bond lengths in [L(X)M]‐substituted pnictanes, dipnictenes and pnictanyl radicals (Al–As 2.4501(7) Å, 2.4554(7) Å; [ 16a ] Ga–As 2.3957(5)‐2.5197(3) Å; [ 16a,18c ] Al–Sb 2.6586(7) Å, 2.7169(7) Å; [ 24 ] Ga–Sb 2.5478(6)–2.8458(13) Å; [ 19,25 ] In–Sb 2.7250(4)‐2.8340(2) Å [ 9c ] ). The As1–C40(Ph) bond lengths in 3 – 5 are comparable to those of Al and Ga‐substituted arsanes Tmp 2 AlAsPh 2 (1.953 Å, 1.966 Å; Tmp = N[C(Me) 2 CH 2 ]CH 2 ), [ 26 ] (Mes*AlAsPh) 3 (1.957(8) Å, 1.971(7) Å, 1.959(7) Å, Mes* = 2,4,6‐ t Bu 3 C 6 H 2 ), [ 27 ] and (Tip 2 Ga) 2 AsPh (1.950(7) Å, Tip = 2,4,6‐ i Pr 2 C 6 H 2 ), [ 28 ] while the Sb1–C40(Ph) bond lengths in 6 – 8 compare well to those of I (2.1716(16) Å), [ 19 ] II (2.1804(18) Å, 2.1748(18) Å), [ 20 ] and [L(Cl)Ga]Sb(Cl)Dip (2.1891(11) Å, 2.1725(13) Å).…”
Section: Resultssupporting
confidence: 89%
“…Recent studies on reactions of group 13 diyls L 1 M (M = Al, Ga, In) with tetraethyldistibane and tetraethyldibismuthane E 2 Et 4 (E = Sb, Bi), as well as L 3 Ga (L 3 = Cy 2 NC[N(2,6-i-Pr 2 C 6 H 3 )] 2 , Cy = C 6 H 11 ) with E 2 Et 4 and E 2 Ph 4 , showed that these reactions proceed with insertion of LM into the E−E bond (oxidative addition) and the formation of complexes of the general type LM(ER) 2 , respectively. 79,90 Obviously, the reduction potentials of the group 13 diyls are too low to further initiate the reduction of the distibane and dibismuthane. In remarkable contrast, reactions of distibanes R 4 Sb 2 with Mg(I) complexes, 47,48 which have been shown in recent years to be very powerful, soluble two-electron reductants, 42 proceeded with reduction of the distibane and subsequent formation of Mgcoordinated, realgar-type Sb 8 cluster-type complexes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While BiCl 3 react with L 1 Ga with the formation of the bismuth-centered radical [L 1 Ga­(Cl)] 2 Bi • 1 , Cp* 2 BiCl undergoes a stepwise oxidative addition/reduction reaction in the presence of L 1 Ga to form the bicyclo­[1,1,0]­butane Bi analogue [{L 1 (Cl)­Ga} 2 -μ,η 1:1 -Bi 4 ] 3 via intermediate formation of a Ga-substituted dibismuthene [L 1 (Cl)­GaBi] 2 2 . In contrast to L 1/3 Ga, which are known to react with dibismuthanes R 4 Bi 2 (R = Et, Ph) with oxidative addition and formation of L 1/3 Ga­(BiR 2 ) 2 , analogous reactions with the stronger reductants [L 1/2 Mg] 2 typically proceed with formation of elemental bismuth . However, complete reduction of the dibismuthane is almost fully avoided when reacting [L 2 Mg] 2 with Ph 4 Bi 2 , yielding the Bi 8 cuneane-type cluster complex [(L 2 Mg) 4 (μ 4 ,η 2:2:2:2 -Bi 8 )] 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Mixtures of mononuclear 2 and distibanes, Sb 2 R 4 (R = Et, Ph), or dibismuthanes, Bi 2 R 4 (R = Et, Ph), form reversible temperature-dependent equilibria between the starting materials and the E–E bond activation products, LGa­(ER 2 ) 2 ( 2 –E 2 R 4 ; E = Sb, Bi; R = Et, Ph), resulting from oxidative addition of the E–E bonds to the Ga I center. , In remarkable contrast, dinuclear 1 cleanly reacts with Sb 2 Et 4 and Bi 2 Ph 4 with E–E bond activation to Cy L 2 (GaER 2 ) 2 (ER 2 = SbEt 2 6 , BiPh 2 7 ) (Scheme ), which were isolated as red crystals in moderate to good yields.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to 3, in which two Ga−C bonds are cleaved, and similar to the reactivity of 2, only one Bi−C bond of BiEt 3 is activated. As observed for 2, bis(gallanediyl) 1 does not react with SbEt 3 even upon prolonged heating of the reaction mixture to 100 °C due to the increased Sb−C bond strength.Mixtures of mononuclear 2 and distibanes, Sb 2 R 4 (R = Et, Ph), or dibismuthanes, Bi 2 R 4 (R = Et, Ph), form reversible temperature-dependent equilibria between the starting materials and the E−E bond activation products, LGa(ER 2 ) 2 (2− E 2 R 4 ; E = Sb, Bi; R = Et, Ph), resulting from oxidative addition of the E−E bonds to the Ga I center.57,58 In remarkable contrast, dinuclear 1 cleanly reacts with Sb 2 Et 4 and Bi 2 Ph 4 with E−E bond activation to Cy L 2 (GaER 2 ) 2 (ER 2 = SbEt 2 6, BiPh 2 7) (Scheme 4), which were isolated as red crystals in moderate to good yields.…”
mentioning
confidence: 99%